Synthesis, Structure and Properties of Benzo[1,2-P.5,4-f＇]- diquinoline Derivatives： A Remarkably Strong Intramolecular C-H...O Hydrogen Bond - 张春 彭晓霞 陈传峰 (中国化学：英文版, 2011)
A series of benzo[1,2-f：5,4-f＇]diquinoline derivatives were synthesized starting from 2,7-diaminoanthracene, and their structures were determined by NMR, MS spectra and X-ray analysis. They showed a remarkably strong intramolecular C--H...O hydrogen bond, which resulted in an unexpected downfield chemical shift of the aromatic proton in CDCl3. Moreover, a significant fluorescent change of molecule lb in the presence of trifluoroacetic acid （TFA） was also observed.